The interlacement of expressive body movement of people with disabilities in school environment (Research, Society and Development, 2021)
The conceptions about people with disabilities (PWD) are discussed in the political scenario to reflect on the contributions of the education of corporal practices that involve the notion of body and the intricate social relations, bringing dance as an essential trigger of possibilities for the perception, awareness and use of the body, and consequently the interrelationships and inter-influences of the individual, with the purpose of dialoguing about the rights of the PWD in educational spaces. In the discursive systematization, the axes of current legislation in the country, corporeity, neuroscience and dance practice are highlighted, bringing to light the importance of the collective actor through experiences envisioned in a specific dance program for this population, which uses principles guiding the process based on the concepts proposed by Dalcroze, Feldenkrais, Laban and Pilates and taking into account three fundamental components for body education through dance: the self, the environment, and the other. The aim is to promote substantial means for emotional, cognitive, physical and social integration in the school environment.